ROAD NETWORK ANALYSIS OF PULAU PINANG USING GIS - Sohari, Hazman (2010)
This project is to study the transportation network and searching on the relationship between data analysis and decision making tools. The formation of the nation's transportation system has been evolutionary. The system now in place is the product of many individual decisions to build or improve its various parts. Therefore, GIS can be used as an effective tool for road information system, which will help the planners and administrators to identify the problems associated with road development activities, location and provision of appropriate facilities, monitoring and maintenance management of the assets. For this, the study on network analysis of Pulau Pinang streets will be done. Observation and collecting data will be involved during this research. The expected findings will be the numerous function in using data and information regarding to the road network analysis.